Gross total resection and survival outcomes in elderly patients with spinal chordoma: a SEER-based analysis - Pham, John; Shaaya, Elias; Rhee, Ben; Kimata, Anna; Ozcan, Evrim E.; Pham, Katie M.; Niu, Tianyi; Sullivan, Patricia; Gokaslan, Ziya L. (Frontiers in Oncology, 2024)
Objective The association between aggressive resection and improved survival for adult spinal chordoma patients has not been well characterized in the geriatric population. Thus, the present study aimed to elucidate the relationship between gross total resection (GTR) and survival outcomes for patients across different age groups. Methods The authors isolated all adult patients diagnosed with spinal chordoma from the 2000-2019 Surveillance, Epidemiology, and End Results database and divided patients into three surgical subgroups: no surgery, subtotal resection (STR), and GTR. Kaplan-Meier curves with a log-rank test were used to discern differences in overall survival (OS) between surgical subgroups. Univariate and multivariate analyses were used to identify prognostic factors of mortality. Results There were 771 eligible patients: 227 (29.4%) received no surgery, 267 (34.6%) received STR, and 277 (35.9%) received GTR. Patients receiving no surgery had the lowest 5-year OS (45.2%), 10-year OS (17.6%), and mean OS (72.1 months). After stratifying patients by age, our multivariate analysis demonstrated that patients receiving GTR aged 40-59 (HR=0.26, CI=0.12-0.55, p<0.001), 60-79 (HR=0.51, CI=0.32-0.82, p=0.005), and 80-99 (HR=0.14, CI=0.05-0.37, p<0.001) had a lower risk of mortality compared to patients undergoing no surgery. The frequency of receiving GTR also decreased as a function of age (16.4% [80-99 years] vs. 43.2% [20-39 years]; p<0.001), but the frequency of receiving radiotherapy was comparable across all age groups (48.3% [80-99 years] vs. 45.5% [20-39 years]; p=0.762). Conclusion GTR is associated with improved survival for middle-aged and elderly patients with spinal chordoma. Therefore, patients should not be excluded from aggressive resection on the basis of age alone. Rather, the decision to pursue surgery should be decided on an individual basis.